Digital economy, environmental regulation and green eco-efficiency—Empirical evidence from 285 cities in China - Yang, Yiwen; Liang, Qiye (Frontiers in Environmental Science, 2023)
Strengthening green eco-efficiency has emerged as one of China's key objectives for its present economic green development. All walks of life have progressively begun to pay attention to how to leverage the rapidly developing digital economy to promote regional green eco-efficiency upgrading. This work first develops a mathematical model to investigate the inherent mechanism of digital economy development on green eco-efficiency enhancement and presents a research hypothesis, which is then followed by a fixed-effects model and a spatial econometric model to evaluate the geographic spillover effect of digital economy development on green eco-efficiency enhancement and the moderating influence of environmental regulation. According to the test results, the growth of the digital economy can greatly increase green eco-efficiency, with environmental legislation acting as a helpful moderator. Additional empirical research revealed that environmental regulation and the development of the digital economy both favourably promote and adjust green eco-efficiency. However, there are various effects of different regions and different time periods, it shows that there are "strong in the East and weak in the west", "weak in the East and weak in the west" and "weak first and then strong". Therefore, each region in China should promote the development of digital economy, accelerate the digitization of industry, and promote the green ecological efficiency of China's industry with the digital economy a grip. At the same time, the regulating role of government environmental regulations should be given full play to narrow the differences between regions and promote the green, coordinated, and sustainable development of each regional economy.